Física y química Propiedades y transformaciones de la materia y de la energía - FUMAGALLI, Laura coord. (ESTRADA, 2000)
CONTENIDO : CANDAS, ALICIA; FERNANDEZ, DIEGO; GORDILLO, GABRIEL; RUBINSTEIN, JORGE; TIGNANELLI, HORACIO; WOLF, ESTHER